Improving Dental Health Knowledge Through Education Using Pop-Up Books for Street Children at Sanggar Alang-Alang Surabaya - Difa Santi Prasetyo; Sunomo Hadi; Agus Marjianto (POLTEKKES KEMENKES PONTIANAK, 2025)
Oral health is an important aspect of maintaining overall health. Street children are a vulnerable group with limited access to health information and services, especially oral health. The problem identified by researchers is the inadequate knowledge of oral health among street children. The purpose of this study was to understand the difference in dental health knowledge before and after providing education using pop-up books to street children. The research method used was a pre-experiment with a one-group pretest-posttest approach. The sample consisted of 36 street children at Sanggar Alang-Alang. Data were collected using questionnaires administered before and after the education session. Data analysis was performed using the Wilcoxon test. The results of the study showed a significant difference in the average knowledge score before the intervention, which was 58.47 ± 9.770, and increased to 84.44 ± 6.947 after the pop-up book intervention (ρ=0.000). Conclusion: there was a difference in dental health knowledge before and after the intervention using pop-up books.